2017
DOI: 10.3892/or.2017.6135
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-411 inhibits malignant biological behaviours of colorectal cancer cells by directly targeting PIK3R3

Abstract: Colorectal cancer (CRC) is the third most common cancer and the fourth leading cause of cancer-related mortality worldwide. Aberrant expression of miRNAs play important roles in the development and progression of various types of cancers by modulating oncogenic and tumour-suppressor pathways. Therefore, exploring the functions of microRNAs (miRNAs) that specifically contribute to CRC tumourigenesis and tumour development would greatly aid in obtaining more information on CRC and provide new targets for its dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…PIK3R3 was observed to be overexpressed in various types of human cancer, including ovarian cancer (32), colorectal cancer (33), glioma (34) and lung cancer (35). A number of previous studies demonstrated that PIK3R3 may be involved in a variety of cellular processes, including cell growth, apoptosis, migration, invasion, metastasis and epithelial-mesenchymal transition (28,36,37). Hence, targeting PIK3R3 may represent as a novel therapeutic method for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIK3R3 was observed to be overexpressed in various types of human cancer, including ovarian cancer (32), colorectal cancer (33), glioma (34) and lung cancer (35). A number of previous studies demonstrated that PIK3R3 may be involved in a variety of cellular processes, including cell growth, apoptosis, migration, invasion, metastasis and epithelial-mesenchymal transition (28,36,37). Hence, targeting PIK3R3 may represent as a novel therapeutic method for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that PIK3R3 is involved in the regulation of the AKT/mTOR signaling pathway (25)(26)(27)(28). Therefore, the present study investigated whether miR-601 may affect the AKT/mTOR signaling pathway in HCC cells.…”
Section: Mir-601 Inactivates the Akt/mtor Signaling Pathway In Hcc Cementioning
confidence: 93%
“…MiR-411 is upregulated in hepatocellular carcinoma, 30 lung cancer, 31,32 and osteosarcoma; 33 on the contrary, it is downregulated in breast cancer, 34,35 renal cell cancer, 36 colorectal cancer, 37 cervical cancer, 38 and bladder cancer. 39,40 Nevertheless, whether miR-411 is dysregulated in ESCC and whether its dysregulation contributes to ESCC oncogenesis has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among these candidates, miR-411 ( Figure 3A) was chosen for subsequent validation, based on its crucial roles in oncogenesis and tumor progression. [30][31][32][33][34][35][36][37][38][39][40] The luciferase reporter assay was carried out to gain more insights into the potential interaction between SNHG8 and miR-411. The results indicated that miR-411 mimics-mediated upregulation of miR-411 ( Figure 3B, P<0.05) significantly weakened the luciferase activity of the SNHG8-wt plasmid in Eca109 and TE-1 cells (P<0.05) but had no such effect on the SNHG8mut plasmid ( Figure 3C).…”
Section: Snhg8 Acts As a Sponge For Mir-411 In Esccmentioning
confidence: 99%
“…Thus, miR-155 could be considered a prognostic marker for overall and disease-free survival ( 147 ). In a recent study, Zhao et al ( 148 ) presented that miR-411 functions as a tumor-suppressive miRNA directly targeting PIK3R3 and indirectly regulating the AKT/mTOR signaling pathway. In other words, an increase of miR-411 would result in the downregulation of PIK3R3 directly and AKT/mTOR indirectly.…”
Section: Prognostic Markersmentioning
confidence: 99%